Ideas for 21st Century Education : Proceedings of the Asian Education Symposium (AES 2016), November 22-23, 2016, Bandung, Indonesia - Hamidah, Ida (Routledge, 2017)
"This work will hold the proceedings of the Asian Education Symposium (AES 2016), held on November 22-23, 2016, in Bandung, Indonesia. Scopes of the conference include: art education, adult education, business education, course management, curriculum research and development, educational foundations, learning/teaching methodologies and assessment, global issues in education and research, pedagogy and ubiquitous learning."--Provided by publisher.